DNA Vaccines
DOI: 10.1385/1-59745-168-1:171
|View full text |Cite
|
Sign up to set email alerts
|

Prime-Boost Strategies in DNA Vaccines

Abstract: Induction of HIV-specific T-cell responses by vaccines may facilitate efficient control of HIV replication. Plasmid DNA vaccines and recombinant fowlpox virus (rFPV) vaccines are promising HIV-1 vaccine candidates, although delivering either vaccine alone may be insufficient to induce sufficient T-cell responses. A consecutive immunization strategy, known as "prime-boost," involving priming with DNA and boosting with rFPV vaccines encoding multiple common HIV antigens, is used to induce broad and high-level T-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 34 publications
2
23
0
1
Order By: Relevance
“…Different forms of heterologous prime-boost vaccines delivered systemically are currently being tested in a number of ongoing preclinical and clinical trials and hold significant promise for eliciting cellular responses and determining the efficacy of T-cell based vaccines (Allen et al, 2000; Amara et al, 2001; Barouch et al, 2000; Belshe et al, 1998; Dale et al, 2006; Gherardi et al, 2003; Hel et al, 2001b; Kent et al, 1998; Neeson et al, 2006; O'Neill et al, 2002; Sharpe et al, 2003; Tritel et al, 2003; Wierzbicki et al, 2002; Wille-Reece et al, 2006). Heterologous prime-boost immunization is a proven strategy that elicits high frequencies of effector and memory T cells, and in particular high-avidity CD8 + CTL that are relevant to vaccine efficacy (Alexander-Miller et al, 1996; Belyakov et al, 2007a, 2007b, 2006b; Derby et al, 2001; Estcourt et al, 2002; Gallimore et al, 1998; Masopust et al, 2006; Ranasinghe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Different forms of heterologous prime-boost vaccines delivered systemically are currently being tested in a number of ongoing preclinical and clinical trials and hold significant promise for eliciting cellular responses and determining the efficacy of T-cell based vaccines (Allen et al, 2000; Amara et al, 2001; Barouch et al, 2000; Belshe et al, 1998; Dale et al, 2006; Gherardi et al, 2003; Hel et al, 2001b; Kent et al, 1998; Neeson et al, 2006; O'Neill et al, 2002; Sharpe et al, 2003; Tritel et al, 2003; Wierzbicki et al, 2002; Wille-Reece et al, 2006). Heterologous prime-boost immunization is a proven strategy that elicits high frequencies of effector and memory T cells, and in particular high-avidity CD8 + CTL that are relevant to vaccine efficacy (Alexander-Miller et al, 1996; Belyakov et al, 2007a, 2007b, 2006b; Derby et al, 2001; Estcourt et al, 2002; Gallimore et al, 1998; Masopust et al, 2006; Ranasinghe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…intra-muscularly, intra-peritoneally, intra-venously and intra-splenicly) it was observed that only the intra-splenic route was the most efficient at inducing specific antibody production after a single injection of DNA. Although it has been verified that a single intra-muscular immunisation with plasmid DNA was sufficient for antibody response (Bohm et al 1996), in other reports at least two DNA injections were required (Davis 1997;Dale et al 2006). These results were supported also by Kasinrerk et al (2002) who demonstrated that only the intra-splenic route could induce a specific antibody response after a single DNA injection.…”
Section: Genetic Immunisation and Delivery Routementioning
confidence: 88%
“…We can not obviously make general predictions based on the immune responses of mice, and the potential of using pVAX1/P48 immunization for the control of contagious agalactia will be evaluated in sheep. The immunization (and challenge) of sheep will take into account the enhancement of humoral immunity through the prime-boost strategy (Dale et al, 2006), that is, priming with pVAX1/P48 and boosting with rP48.…”
Section: Discussionmentioning
confidence: 99%